A reassertion of the law regarding relative grounds for refusal of registration of EU trade marks. (16th January 2019) - Tong, Michelle S H
Abstract: European Union Intellectual Property Office, Opposition No B 2 811 415, Viña Concha y Toro S.A. v Licores del Papa y El Diablo, S.A. de C.V, 11 October 2018 The European Union Intellectual Property Office rejected the opposition filed by the holder of the 'Casillero del Diablo', 'Casillero del Diablo, Wine Legend' and 'Diablo' trade marks against registration of 'Papadiablo' as an EU trade mark.